Health literacy, health status and health behaviors of German students- study protocol for the "Healthy Habits" cohort study - Martin Lange; Alexandra Löwe; Gerrit Stassen; Andrea Schaller (BMC, 2021)
Abstract Background The emerging adulthood is traditionally viewed as a time of optimal health, but also as a critical life span, characterized by changing life circumstances and the establishment of an individual lifestyle. Especially university life seems to hold several challenges impeding the manifestation of a health supporting manner, as many students tend to show a poorer health behavior and a higher amount of health-related problems than comparable age groups. This, along with a steady growth of the higher education sector, brings increased attention to the university setting in the context of prevention. To date, there are few empirical longitudinal and coherent cross-sectional data on the status of students' health literacy, health status, and health behaviors, and on the impact of the study format on students' health. The aim of this prospective cohort study is to reduce this research gap. Methods Starting during winter semester 2020/21, the prospective cohort study collects data on health literacy, health status and health behavior on a semester-by-semester basis. All enrolled students of the IST University of Applied Sciences, regardless of study format and discipline, can participate in the study at the beginning of their first semester. The data are collected digitally via a specifically programmed app. A total of 103 items assess the subjectively perceived health status, life and study satisfaction, sleep quality, perceived stress, physical activity, diet, smoking, alcohol consumption, drug addiction and health literacy. Statistical analysis uses (1) multivariate methods to look at changes within the three health dimensions over time and (2) the association between the three health dimensions using multiple regression methods and correlations. Discussion This cohort study collects comprehensive health data from students on the course of study. It is assumed that gathered data will provide information on how the state of health develops over the study period. Also, different degrees of correlations of health behavior and health literacy will reveal different impacts on the state of students' health. Furthermore, this study will contribute to empirically justified development of target group-specific interventions. Trial registration German Clinical Trials Register: DRKS00023397 (registered on October 26, 2020).